Democratic criteria and American political reality - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2021)
The author studies social-economic consequences of the electoral campaign in the United States for the future of the America’s Commonwealth and geopolitical consequences. The author counsel to research views of the end of the America’s century and that United States will be never the role of the leader of the west world. At the same time the author invites to assay the arguments of those researches, who counsel, that the United States will be the most powerful countryeconomically, industrially and militarily having creating functioned democratic system are able to mobilise the potential, which will recover the lost positions of the United States in the world.